Experimental investigation of inductively coupled plasma etching on cemented carbides. (April 2019) - Lian, Yunsong; Mu, Chenliang; Xie, Chaoping; Yao, Bin
Abstract: Experimental investigation of inductively coupled plasma etching on cemented carbides was proposed in this paper. SF6 /O2 /Ar gases were selected as the etching gases. The effect of five etching parameters on the etching process was also analysed by laser scanning confocal microscope. Combined with the two indexes of etching rate and etched surface roughness, the optimal etching process parameters were obtained: SF6 /O2 /Ar gas flow ratio of 20/60/10 sccm, inductively coupled plasma power (ICP power) of 800 W, radio frequency power (RF power) of 250 W, gas pressure of 3 Pa, and substrate temperature of 60 °C. The results showed that etching rate significantly increased with the increase of RF power, ICP power, and substrate temperature, especially RF power. The etching rate slowly increased as oxygen flow rate in SF6 /O2 /Ar gas flow increased. The effect of gas pressure on etching rate showed a large fluctuation, which first increased and then decreased. Besides, substrate temperature and SF6 /O2 /Ar gas flow ratio had little effect on the etched surface roughness. However, the etched surface roughness significantly increased as ICP power and gas pressure increased. The effect of RF power on the etched surface roughness presented a fluctuating change, first increasing and then decreasing. Highlights: Inductively coupled plasma etching on cemented carbides was investigated. Effect of different etching parameters on the etching process was analysed. Based on two indexes, optimal etching process parameters were obtained. Etching rate significantly increased with the increase of RF power. Surface roughness significantly increased as ICP power and gas pressure increased.